Supervision and Water Depth Automatic Control of an Irrigation Canal - Rijo, Manuel (2012)
A supervisory and control system developed for a Portuguese irrigation canal system equipped with motorized sluice gates and buffer reservoirs is presented. The article discusses the development and tuning of the canal system’s controllers: manual controllers - for direct control of gate position and gate flow controllers, which maintain discharge at pre-defined values; automatic controllers - for water depth control upstream from check structures. System hydraulics was simulated using an unsteady flow open-channel model based on the complete Saint-Venant equations. After field calibration and validation, the model was used for tuning the water depth controllers. The automatic upstream water depth control is based on local proportional-integral (PI) controllers. Controller gains were determined using optimization tools provided by the hydraulic simulator. These procedures tune the controller parameters globally, considering a given set of inflow variations. Finally, the paper presents simulated control tests results and an analysis of controller performances. Under the test conditions, the controller was able to drive water levels back to their setpoint rapidly and without instabilities and also guaranteeing stable gates movement.